Phytochemical analysis of roots among various genotypes across different age groups in rauwolfia serpentina (l.) Benth by high performance liquid chromatography - PAMPOSH MOHAN KOUL; BASANAGOUDA SANGANAGOUDA JANAGOUDAR (International Journal of Pharma and Bio Sciences, 2017)
Rauwolfia serpentina contains 50 indole alkaloids and most of the total alkaloid content is present mainly in root bark. For centuries, roots of Rauwolfia serpentina have been used in traditional Unani and Ayurvedic medicine as a valuable remedy against many complex diseases. The present investigation was carried out in relevance to isolation of bioactive constituents from the roots amongst diverse genotypes across different age groups of Rauwolfia serpentina by using High Performance Liquid Chromatography analysis. The peaks were identified using reference standard of reserpine and the content of reserpine in methanolic root extract was determined using area under the curve of sample and reference standard. The combination pertaining genotype SRS 1 at 18 months was found significantly superior in recording the highest reserpine content (3.039 ± 0.03%) whereas, the lowest was noticed in genotype SRS 3 (1.818 ± 0.09%) for the same age group. The High Performance Liquid Chromatography evaluation illustrated that the principal bioactive component is reserpine. Root biomass along with the formation of new adventitious roots has a very direct effect in the per cent reserpine content of the roots. This is the foremost attempt to reveal the High Performance Liquid Chromatography analysis of roots amid various genotypes across different age groups of Rauwolfia serpentina.